See Our team

Wondering how we keep quality?

Got unsolved questions?

Ask Questions

Engineering
GATE
CBSE
NCERT
Psychology
English
Computer
Constitution
Astrology
Yoga
Economics
Physics
Biology
Electronics
Microprocessor
Career
Interview
Anatomy
Botany

## Using laws of set theory show that

Using laws of set theory show that A – (A – B) = A – (A ∩ B)By:Nikhil-bharadwaj

Taged users:

Likes:

Be first to like this question

Dislikes:

Be first to dislike this question

Talk about thisDelete|Like|Dislike|

## Answers

Sol:A – (A – B) = A – (A ∩ B1) [i.e A – B = A ∩ B1]= A ∩ (A ∩ B1)1 [i.e A – B = A ∩ B1]

= A ∩ (A1 U B) [Demorgan’s Law]

= (A ∩ A1) U (A ∩ B) [Distributive Law] =ø U (A ∩ B) [i.e. A ∩ A1 = ø]

= A ∩B

Nikhil-bharadwaj

Likes:

Be first to like this answer

Dislikes:

Be first to dislike this answer

Talk about this|Once you have earned teacher badge you can edit this questionDelete|Like|Dislike|

------------------------------------

## Can you help us to add better answer here? Please see this